2002
DOI: 10.1053/jlts.2002.34892
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for hepatocellular carcinoma: Comparison of the proposed UCSF criteria with the Milan criteria and the Pittsburgh modified TNM criteria

Abstract: We previously proposed modified staging criteria for predicting acceptable outcome after orthotopic liver transplantation (OLT) for hepatocellular carcinoma (HCC). These were solitary tumor <6.5 cm, or three or fewer nodules with the largest lesion <4.5 cm and total tumor diameter <8 cm, without gross vascular invasion (University of California, San Francisco [UCSF] criteria). In this study, we further evaluated the performance of the Milan criteria (solitary tumor <5 cm, or three or fewer lesions none >3 cm),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
271
3
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(292 citation statements)
references
References 28 publications
10
271
3
8
Order By: Relevance
“…Our study results were consistent with previous studies that showed no survival differences in patients with HCC for both those that met and those exceeded the Milan criteria [9,16,18] and for those that met both the Milan and UCSF criteria [17,19]. Although the UCSF criteria have been shown to be associated with a longterm survival similar to the Milan criteria [23][24][25], little is known with regard to the outcomes of patients with HCC that exceed the UCSF criteria. In one of the largest series, Duff et al reported a 3-year survival of 83 % for those that met the UCSF criteria and 48 % for those exceeded the UCSF criteria [20].…”
Section: Discussionsupporting
confidence: 82%
“…Our study results were consistent with previous studies that showed no survival differences in patients with HCC for both those that met and those exceeded the Milan criteria [9,16,18] and for those that met both the Milan and UCSF criteria [17,19]. Although the UCSF criteria have been shown to be associated with a longterm survival similar to the Milan criteria [23][24][25], little is known with regard to the outcomes of patients with HCC that exceed the UCSF criteria. In one of the largest series, Duff et al reported a 3-year survival of 83 % for those that met the UCSF criteria and 48 % for those exceeded the UCSF criteria [20].…”
Section: Discussionsupporting
confidence: 82%
“…For patients not meeting the MC, the rates of mVI and grade 3 and 4 tumors significantly increase (35%-56% and 38%-50%, respectively). 26,48 Similar rates of histological markers of tumor aggressiveness and poor prognoses have been detected in patients slightly exceeding the MC, such as patients meeting the University of California San Francisco criteria, 52,84 even though a significant proportion of patients meeting the University of California San Francisco criteria are meeting the MC as well. 24,34,47,51 We identified 10 studies 16,18,26,28,47,48,51,52,63,72 reporting frequency data for mVI and tumor grades in patients meeting or not meeting the MC, and a meta-analysis of the odds ratios was performed accordingly (Fig.…”
Section: And Transplantation For Patients With Hcc Beyond Conventimentioning
confidence: 78%
“…The meta-analysis included 19 studies 2,15,16,19,26,33,35,39,40,42,46,48,[53][54][55]57,63,67,84 that used different methodologies to compare the overall survival of patients meeting the MC and patients exceeding the criteria at the time of the explant pathology examination; 3949 patients were also stratified by the graft origin (deceased or living donors).…”
Section: And Transplantation For Patients With Hcc Beyond Conventimentioning
confidence: 99%
“…Yao et al compared the then proposed UCSF criteria with the Milan criteria and the Pittsburgh criteria in 70 patients transplanted for HCC. 17 The difference in survival between 24 patients beyond Milan criteria and 46 patients within Milan criteria was not significant. Fourteen patients (20%) exceeded the Milan criteria but met the UCSF criteria Poon et al from the University of Hong Kong reported that hepatitis C and microscopic venous invasion, in addition to tumor size and multifocality were independent predictors of recurrence in 247 cirrhotic patients undergoing resection or transplantation.…”
Section: Beyond Tumor Size and Numbermentioning
confidence: 88%